The employability skills of business graduates in Syria: Do policymakers and employers speak the same language?. Issue 1 (9th January 2017) - Ayoubi, Rami M.; Alzarif, Kahla; Khalifa, Bayan
Abstract : Purpose: The purpose of this paper is to compare the desired employability skills of business graduates in Syria from the perspective of both higher education policymakers and employers in the private sector. Design/methodology/approach: Interviews were conducted with 12 higher education policymakers and managers from the business sector. Content analysis was utilized to analyse the content of the interviews and the strategic priorities of the higher education sector in Syria. Findings: Results revealed that although higher education policymakers focus more on societal, public and thinking skills for business graduates, the business sector focusses more on individual, private and practical skills. Accordingly, a comparative tool that aligns the two perspectives was developed in the study. The tool, based on the contradicting employability skills, identified four types of business graduates: leader, collective, technical and trainee. Research limitations/implications: The study is limited by data collected before the current political instability in Syria in 2012. The data were collected only from official documents and interviews with policymakers and employers. Students were not part of the study. Practical implications: The managerial tool developed at the end of the study will help both policymakers and the private sector to statistically allocate business graduates for better planning. The study provides recommendations to the different stakeholders in the higher education sector in Syria. Originality/value: Although the majority of the previous literature raises the voices of the business sector, this study is one of the first studies that aligns the discrepant perspectives of the higher education and business sectors. The managerial tool developed in the study is original and usable by policymakers and the business sector, and it is subject to further development.